2009
DOI: 10.1158/0008-5472.can-09-1568
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Antioxidant and DNA Repair Gene Expression in Normal Airway Epithelium Associated with Lung Cancer Diagnosis

Abstract: In previous studies, we reported that key antioxidant and DNA repair genes are regulated differently in normal bronchial epithelial cells of lung cancer cases compared with non-lung cancer controls. In an effort to develop a biomarker for lung cancer risk, we evaluated the transcript expressions of 14 antioxidant, DNA repair, and transcription factor genes in normal bronchial epithelial cells (HUGO names CAT, CEBPG, E2F1, ERCC4, ERCC5, GPX1, GPX3, GSTM3, GSTP1, GSTT1, GSTZ1, MGST1, SOD1, and XRCC1). A test com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 43 publications
0
56
0
Order By: Relevance
“…However, increasing evidence suggests that GPx3 also possesses tumor suppressor activity (5,9,(22)(23)(24)(25)(26)(27)(28)(29). In this study, GPx3 carries out tumor suppressor signaling at least partly through the activation of PIG3, which is a protein associated with the generation of ROS that induces cell death.…”
Section: Discussionmentioning
confidence: 70%
“…However, increasing evidence suggests that GPx3 also possesses tumor suppressor activity (5,9,(22)(23)(24)(25)(26)(27)(28)(29). In this study, GPx3 carries out tumor suppressor signaling at least partly through the activation of PIG3, which is a protein associated with the generation of ROS that induces cell death.…”
Section: Discussionmentioning
confidence: 70%
“…This biomarker improves diagnostic accuracy when combined with traditional diagnostic bronchoscopy (16), and is independent of clinical factors as a diagnostic risk factor (17). The concept that gene expression in normal airway epithelium can be used as a biomarker of lung cancer was also used by Blomquist and colleagues to identify 14 genes (including antioxidant and DNA repair genes) whose expression was altered in brushings of normal bronchial epithelium of patients with lung cancer versus those without lung cancer (18).…”
Section: Transcriptomic Studies Of Differential Gene Expression In Thmentioning
confidence: 99%
“…This approach is based on the paradigm that the airway gene expression response to smoking reflects a gene-by-environment interaction that could identify that subset of smokers that are at highest risk for future lung cancer development. As proof of concept, Blomquist et al 35 found that variability in the expression level of 14 antioxidant and DNA repair genes in the cytologically normal bronchial epithelium could distinguish smokers with and without lung cancer, with an area under the curve of 0.87 in an independent cross-sectional cohort of 40 patients. While these findings suggest that an aberrant airway gene expression response to smoking associates with lung cancer, these studies have yet to be conducted in prospective studies of high-risk smokers where airway gene expression changes are observed prior to lung cancer development.…”
Section: Using the Transcriptome To Develop Biomarkers For Lung Cancementioning
confidence: 99%